Manifestations and intensity of psychological stress of the family members of incurable cancer patients - Koval, Iryna (Psychosomatic Medicine and General Practice, 2016)
The study has looked into the manifestations and intensity of psychological stress experienced by family members of incurable cancer patients. Of the surveyed family members 60.7% demonstrated adjustment disorders, which psychologically were manifest in threshold distress level and high psychological and social stress levels, as well as psychological pathologic symptoms, such as anxiety and depression, obsessive-compulsive symptoms, interpersonal sensitivity and somatic health problems. The psychological responses of the family members were directly linked to the patient’s condition, whereby changes in the somatic and psychological condition of the patient acted as “triggers” of psychological responses of the family members.